2015
DOI: 10.1590/0104-07072015002700013
|View full text |Cite
|
Sign up to set email alerts
|

Procedures after exposure to biological material in a specialized cancer hospital

Abstract: Occupational accidents involving biological material are a concern for healthcare facilities due to the severe harm they may cause to healthcare workers. This cross-sectional study's aim was to identify the behavior reported by nursing professionals in response to biological material exposure in a cancer hospital located in São Paulo, Brazil. The population was composed of 441 professionals. The hospital's Institutional Review Board approved the project. Of the 441 interviewed subjects, 82 (18.6%) reported exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 22 publications
0
9
1
11
Order By: Relevance
“…17 Among the sectors where the accidents occurred we see the presence of the Surgical Center and also of the Central of Sterilized Material, different from other studies that highlight a greater occurrence of accidents in the Intensive Care Unit and Medical Clinic. 17 For the presentation of the study's qualitative analysis, the discussion of the Subcategories of the Category Motivations for self-reported actions after the occurrence of the work accident related to the inventory of the RU is presented in Table 2.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…17 Among the sectors where the accidents occurred we see the presence of the Surgical Center and also of the Central of Sterilized Material, different from other studies that highlight a greater occurrence of accidents in the Intensive Care Unit and Medical Clinic. 17 For the presentation of the study's qualitative analysis, the discussion of the Subcategories of the Category Motivations for self-reported actions after the occurrence of the work accident related to the inventory of the RU is presented in Table 2.…”
Section: Discussioncontrasting
confidence: 81%
“…[14][15] Here, the work-related accidents occurred in their totality by female professionals, other studies present similar data, which indicate that most of the reported accidents occur among female professionals. 14,17 Concerning the age of the injured professionals, the majority of professionals were within an age group from 25 and 35 years old, who would be professionals with less time of experience in the profession, they were also found in other studies, where most of the accidents occur in the younger age groups. 17 Among the sectors where the accidents occurred we see the presence of the Surgical Center and also of the Central of Sterilized Material, different from other studies that highlight a greater occurrence of accidents in the Intensive Care Unit and Medical Clinic.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…[3][4] Prevention of accidents and diseases must be a priority in work environments; however, given the impossibility of preventing accidents, every institution must be prepared to assist victims by adopting a protocol for exposure, offering support to workers and reporting accidents. 5 In general, educational interventions are recommended to encourage the use of SPs, reporting of work accidents (WAs), risk management, enforcement of SPs, proper availability of personal protective equipment (PPE) and good working conditions to fulfill the demand, as these factors influence adherence to SPs. 6 Among the strategies for educational intervention, videos can be used for this purpose as they are easy to access, use and handle; also their audiovisual characteristics help memorize information and attract interest of viewers.…”
Section: Introductionmentioning
confidence: 99%
“…5 Após a exposição decorrente de um ATMB, os profissionais devem procurar atendimento especializado a fim de detectar o seu status sorológico, o risco de infecção e receber o tratamento profilático, quando indicado, de acordo com o tipo de exposição. 6 Entretanto, muitos profissionais não reconhecem sua vulnerabilidade à infecção e aos riscos ocupacionais advindos de um ATMB. 4 Este tipo de acidente acarreta diversas consequências aos trabalhadores, tais como: preocupação, perda de sono, ansiedade, medo, descontrole emocional, culpa, problemas no relacionamento com a família e desconforto devido à quimioprofilaxia.…”
unclassified